DUKUNGAN KELUARGA DENGAN KEJADIAN PREEKLAMSI PADA IBU HAMIL - Widyasih Sunaringtyas; Diana Rachmania (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Family support during pregnancy is often perceived as an unimportant form, many pregnant women do ante natal care without being accompanied by their families so they feel alone and low motivation to carry out examinations. Ante Natal Care is very necessary to determine health status and detect risks that occur during pregnancy. The purpose of this study was to determine the relationship between family support and the incidence of pre-eclamsia in pregnant women. The research design used correlation with a cross sectional approach with cross sectional data collection methods. The study population was all pregnant women who were at the Kasembon Public Health Center, Malang Regency, respondent 42 personused total sampling technique. The research instrument was a family support questionnaire and a checklist form for the incidence of pre-eclampsia. The results showed that family support was less than 45%, the incidence of mild pre-eclamsia was 45%. Analysis of the relationship using the statistical test Rho Spearman get p value: 0.002 <0.05 so that H0 is rejected H1 is accepted. Family support for pregnant women can increase motivation to perform Ante Natal Care and the health status of the mother is immediately known, especially if pregnancy complications occur. One of the complications of pregnancy is preeclampsia, it can be detected early so that the occurrence of eclampsia can be known. Therefore, it is necessary to increase family support for pregnant women in order to increase their motivation to know health status during pregnancy.